2001
DOI: 10.1089/104303401750195926
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Heme Oxygenase 1 cDNA by a Replication-Deficient Adenovirus Enhances Interleukin 10 Production from Alveolar Macrophages That Attenuates Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: By using a direct, intratracheal inoculation of an adenovirus encoding heme oxygenase 1 (Ad.HO-1), model gene therapy for acute lung injury induced by inhaled pathogen was performed. Data demonstrated that Ad.HO-1 administration is as effective as the pharmacologic upregulation of the endogenous HO-1 gene expression by hemin to attenuate neutrophilic inflammations of the lung after aerosolized lipopolysaccharide (LPS) exposure. Interestingly, immunohistochemical analysis revealed that the HO-1 gene was transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 51 publications
3
84
0
Order By: Relevance
“…31,32 It has also been demonstrated that overexpression of exogenously inserted HO-1 cDNA in gene transfer vectors confer therapeutic benefit on a murine model of hyperoxia 33 or LPS induced lung injury. 34 These experimental results demonstrated by using relatively simple proinflammatory stimuli (LPS, hyperoxia, hydrogen peroxide, TNF-␣) are consistent with the concept that HO-1 overexpression has the ability to attenuate lung injury induced by a variety of airborne pathogens by modulating cytokines expression profiles via a change in the p38MAPK activity, by decreasing inflammatory cell migrations into the lung, or by suppressing apoptotic deaths of respiratory epithelial cells induced by reactive oxygen species.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…31,32 It has also been demonstrated that overexpression of exogenously inserted HO-1 cDNA in gene transfer vectors confer therapeutic benefit on a murine model of hyperoxia 33 or LPS induced lung injury. 34 These experimental results demonstrated by using relatively simple proinflammatory stimuli (LPS, hyperoxia, hydrogen peroxide, TNF-␣) are consistent with the concept that HO-1 overexpression has the ability to attenuate lung injury induced by a variety of airborne pathogens by modulating cytokines expression profiles via a change in the p38MAPK activity, by decreasing inflammatory cell migrations into the lung, or by suppressing apoptotic deaths of respiratory epithelial cells induced by reactive oxygen species.…”
Section: Introductionsupporting
confidence: 82%
“…Consistent with this observation, neutrophil migration into the lung following an intratracheal challenge of LPS was attenuated when animals breathed air containing CO, but that was not attenuated in animals lacking p38 MAPK. 28,30 Inoue et al 34 have also demonstrated that neutrophil migration to the lung following LPS inhalation was markedly attenuated by pre-administration of an endogenous HO-1 inducer, hemin, or an Ad expressing HO-1 in mice, and further demonstrated that IL-10 overproduction by macrophages was essential for suppressed neutrophilic inflammation. Together, these data suggest that overexpression of HO-1 results in CO production, which modifies cytokine profiles within both inflammatory and respiratory epithelial cells, thus suppressing neutrophil migration into the lung in response to LPS.…”
Section: Discussionmentioning
confidence: 95%
“…For example, carbon monoxide has been shown to mediate the antiinflammatory effects of IL-10 in a mouse model of septic shock (35). In addition, exogenous administration of HO-1 increases IL-10 production in macrophages, which leads to the resolution of neutrophilic migration in the lung after lipopolysaccharide administration (36). In contrast, HO-1 does not seem to play a significant role in the antiinflammatory activity of IL-10 in human monocytes or macrophages (37,38), and an autoregulatory feedback loop is present in lipopolysaccharide-stimulated human monocytes, involving proinflammatory cytokines and IL-10 (39), with a likely predominant role of TNF␣ (40).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 overexpression has shown antiinflammatory or immunomodulatory effects in models of acute disease (10,16,36,(45)(46)(47). Less is known about the possible role of this enzyme in chronic inflammatory diseases, which involve complex interactions between different cell populations and a wide range of mediators.…”
Section: Discussionmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript that cause oxidative stress and/or in response to environmental stress [5][6][7][8]. For example, increased HO-1 expression has recently been found in the alveolar spaces in the resident macrophages of smokers [9].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%